1980
DOI: 10.1055/s-2007-1022440
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Development of the Heart* - Part I: Normal Development

Abstract: The formation of the relief of cardiac septa occurs in connexion with the development of shape of the external cardiac wall. Changes in the form of the external cardiac wall precede changes in the internal cardiac wall. The originally straight tubular heart is angulated at typical sites during cardiac looping. At the site of angulations the primary circular cross-section is deformed to an oval and is thereby narrowed. This deformation causes a growth of the endocardial and subendocardial tissue along the long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…If this R-loop transforms the straight heart tube into a C-shaped structure (De Haan, 1965;Stalsberg, 1970), then the lateral displacement of the arterial and venous poles of the heart tube and the "shortening" of the distance between these two areas (following the cranio-caudal axis) determine the conversion into a S-shaped conformation in which embryonic atria become cranial to the ventricles (De la Cruz, 1998;Taber, 1998). Most authors agree in considering the end of the S-shaped heart phase as the end of cardiac looping (De la Cruz, 1998;Taber, 1998), whereas others would like to consider that the looping is not really terminated until cardiac chambers are completely aligned and septated (Steding and Seidl, 1980;Männer et al, 1993;Männer, 2000; Cardiac looping and layering events are summarized in Figure 4). …”
Section: The Role Of Tissue Interactions and Heart Looping In Cardiacmentioning
confidence: 99%
“…If this R-loop transforms the straight heart tube into a C-shaped structure (De Haan, 1965;Stalsberg, 1970), then the lateral displacement of the arterial and venous poles of the heart tube and the "shortening" of the distance between these two areas (following the cranio-caudal axis) determine the conversion into a S-shaped conformation in which embryonic atria become cranial to the ventricles (De la Cruz, 1998;Taber, 1998). Most authors agree in considering the end of the S-shaped heart phase as the end of cardiac looping (De la Cruz, 1998;Taber, 1998), whereas others would like to consider that the looping is not really terminated until cardiac chambers are completely aligned and septated (Steding and Seidl, 1980;Männer et al, 1993;Männer, 2000; Cardiac looping and layering events are summarized in Figure 4). …”
Section: The Role Of Tissue Interactions and Heart Looping In Cardiacmentioning
confidence: 99%
“…This convergence permits correct align-ment of the outflow septum with the atrioventricular and ventricular septa in the final stage of ventricular septation (1). Experimental studies have suggested that abnormal looping and convergence can cause malalignment of inflow and outflow segments of the hearts (7,(19)(20)(21). Cardiac neural crest ablation results in doubleoutlet right ventricle or rightward displacement of the PTA in 80% of the affected hearts after neural crest ablation (1,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…In the third variant, cardiac looping covers the phases of dextral-looping, early s-looping, and late s-looping (Patten, 1922;Steding and Seidl, 1980;Männer et al, 1993). Thereby, the end point of looping morphogenesis is set around a stage at which the main regional divisions of the mature heart and the primordium of the great arterial trunks become definitively established.…”
Section: Terminology Of Cardiac Loopingmentioning
confidence: 97%